Photodynamic therapy with acai (Euterpe oleracea) and blue light in oral cells: A spectroscopic and cytotoxicity analysis - Silva Junior, Zenildo Santos; Santos, Lucas Andreo Dias; Gonçalves, Marcela Leticia Leal; Gallo, Juliana Maria Altavista Sagretti; Silva, Tamiris; Motta, Lara Jansiski; Santos, Elaine Marcílio; Horliana, Anna Carolina Ratto Tempestini; Fernandes, Kristianne Porta Santos; Mesquita‐Ferrari, Raquel Agnelli; Bussadori, Sandra Kalil (Journal of biophotonics, 2023)
Objective To evaluate the potential of photodynamic therapy (PDT) with blue light‐emitting diode (LED) 460 nm at 25, 50 and 100 J/cm2 using three concentrations of acai extracts (100, 40, and 10 mg/ml), in the proliferation and viability of head and neck tumor lines (SCC9). Methods Three groups of cells were analyzed for 3 days in an in vitro assay with MTT (3‐ (4,5‐dimethylthiazol‐2‐yl) ‐2,5, ‐diphenyltetrazolium bromide) and crystal violet: cells in the absence of acai extract and PDT (control group); cells in the presence of acai extract and no light; and cells in the presence of acai extract and LED blue light (PDT groups). Results When using acai as a PS combined with blue LED (460 nm, 0.7466 cm2, 1000 mW/cm2) and irradiation at 25, 50, and 100 J/cm2, after 72 h, cell viability (p < 0.0001 vs. control, p = 0.0027 vs. 100 mg/ml açai group, p = 0.0039 vs. 40 mg/ml açai group, p = 0.0135 vs. 10 mg/ml açai group; One‐Way ANOVA/Tukey) and proliferation (p < 0.05, One‐Way ANOVA/Tukey) decreased. Conclusion The acai in question is a potential photosensitizer (PS), with blue light absorbance and efficacy against head and neck tumor lines (SCC9). The study aimed to evaluate the potential of photodynamic therapy (PDT) with blue light‐emitting diode (LED) 460 nm at 25, 50 and 100 J/cm2 using three concentrations of acai extracts, as a photosensitizer (PS) (100, 40, and 10 mg/ml), in the proliferation and viability of head and neck tumor lines (SCC9). This in vitro study shows that acai has anti tumorigenic potential for the proliferation of this cell line, causing cell viability reduction when associated with a blue LED for PDT, as shown in the figure. The acai in question is a potential PS, with blue light absorbance. More studies with this PS should be encouraged to verify its clinical performance.